How to win friends and influence people in the digital age - Cole, Brent; Dale Carnegie & Associates (New York : Simon & Schuster, 2011)
An up-to-the-minute adaptation of Dale Carnegie's timeless, commonsense approach to communicating. In today's world, where more and more of our communication takes place across wires and screens, Carnegie's lessons have not only lasted but become all the more critical.
Why Carnegie's advice still matters -- Essentials of engagement. Bury your boomerangs ; Affirm what's good ; Connect with core desires -- Six ways to make a lasting impression. Take interest in others' interests ; Smile ; Reign with names ; Listen longer ; Discuss what matters to them ; Leave others a little better -- How to merit and maintain others' trust. Avoid arguments ; Never say,'You're wrong' ; Admit faults quickly and emphatically ; Begin in friendly way ; Access affinity ; Surrender the credit ; Engage with empathy ; Appeal to noble motives ; Share your journey ; Throw down a challenge -- How to lead without resistance or resentment. Begin on a positive note ; Acknowledge your baggage ; Call out mistakes quietly ; Ask questions instead of giving direct orders ; Mitigate fault ; Magnify improvement ; Give others a fine reputation to live up to ; Stay connected on common ground.
Includes bibliographical references.
Keywords: Influence (Psychology); Interpersonal relations; Interpersonal communication; Success